What Do We Mean by Accumulation? Advancing Conceptual Precision for a Core Idea in Gerontology. (16th February 2016) - Ferraro, Kenneth F; Morton, Patricia M
Abstract: In recent decades, the concept of accumulation has gained prominence in research on aging, health, and social stratification. Accumulation is now studied in multiple disciplines, revealing that cumulative processes are crucial to understanding patterns of differentiation over the life course. Although this research has demonstrated the empirical value of studying accumulation, the concept has taken on different and sometimes inconsistent meanings. To address these inconsistencies, we propose an interdisciplinary conceptual framework of accumulation that focuses on objects, timing, thresholds, de-accumulation, and the levels and consequences of accumulation. Providing a coherent framework of accumulation will aid conceptual precision, guide future research, and inform public policies related to aging and the life course.